MON-605 Serum CD163, but Not Gal-3, Predicts Response to Liraglutide Therapy in Obese Patients - Mat, Arimin (J Endocr Soc, 2020)
Liraglutide is a GLP-1 Receptor Agonist licensed to treat T2DM and obesity. Soluble CD163 (sCD163) is a marker of macrophage activation, the integral immunological component in inflammation associated with obesity. Gal-3 is a β-galactoside-binding lectin that has been implicated in the development of cardiovascular diseases and insulin resistance. Recent studies have suggested that Gal-3 is raised in obesity with levels correlating with markers of inflammation. In this study, we aim to elucidate if the levels of sCD163 and Gal-3 can be used to predict treatment outcomes of Liraglutide in obese patients. Thirty-four obese patients (58.8% female; 44.1% diabetic) were enrolled for 12-week Liraglutide therapy. Anthropometric parameters were assessed before and after. Serum levels for sCD163 and Gal-3 were measured using ELISA. Pre-treatment age (mean ± SD) was 52.41 ± 10.74y, BMI was 44.97±7.71 kg/m(2), HbA1c was 47.18±15.96 mmol/mol, sCD163 was 284059.20 ± 71859.88 pg/ml and Gal-3 was 6584.83 ± 3477.59 pg/ml. Post-treatment, BMI reduced to 43.19±7.92 kg/m(2) (p < 0.001), HbA1c to 43.59±16.00 mmol/mol (p<0.001), sCD163 to 249130.45 ± 57972.85 pg/ml (p<0.001) and Gal-3 to to 6254.23 ± 3282.66 pg/ml (p<0.03). We found that pre-treatment sCD163 levels correlate weakly with BMI and HbA1c (r=0.3 & 0.4) while Gal-3 correlates moderately with age only (r=0.36). Percentage of changes in HbA1c (∆HbA1c) correlates strongly with ∆sCD163 (r=0.6). Levels of pre-treatment sCD163 correlates strongly with higher ∆sCD163 (r=0.7). Changes in BMI post-treatment (∆BMI) is negatively correlated with initial sCD163 levels (r=-0.3) and is not correlated with ∆sCD163. Liraglutide treatment leads to significant improvement in sCD163 and Gal-3 levels in obese patients. Patients with high HbA1c have high levels of sCD163. Reduction in sCD163 predicts reduction in HbA1c. Higher initial sCD163 levels predicts poor weight improvement. Patients most likely to have reduction in sCD163 are the ones with higher initial sCD163 levels. We conclude that sCD163 but not Gal-3 levels can predict response to liraglutide in obese patients.